Genotype x environment interactions and QTL clusters underlying dough rheology traits in triticum aestivum L. - Prashant, Ramya; Mani, Elangovan; Rai, Richa; Gupta, R. K.; Tiwari, Ratan; Dholakia, Bhushan B.; Oak, Manoj; Roeder, Marion; Kadoo, Narendra Y.; Gupta, Vidya (Journal of Cereal Science, 2015)
Genetic dissection of dough rheology traits (DRT) in hexaploid wheat was carried out using nine mixograph characters evaluated in two consecutive years in three agro-climatic zones in India in an RIL population (HI977 x HD2329). Pearson correlations determined in each year-location indicated 15 stable trait inter-relationships among them but inconsistent correlations with loaf volume (LV) were observed. Using AMMI analysis we derived patterns in G x E interactions (GEI) indicating 6-47% contribution for the DRT. Composite interval mapping using a linkage map of 202 SSR markers identified 144 DRT QTLs of which, 96 were detected in single- and the rest in two to five year-locations. Sixteen QTL clusters located on ten chromosomes were identified and only three of them on chromosomes 1B, 5B and 6D involved LV QTLs. For each trait, majority of the DRT QTLs detected in single as well as multiple environments showed location-specificity and suggested that owing to GEI, breeding for wheat dough quality might need careful selection of QTLs targeted for individual agro-climatic zones. The inconsistent correlations of DRT and LV and differential locations of their QTLs in this population corroborated that using dough rheological traits alone to predict LV might pose challenges during wheat improvement. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: AMMI analysis; Dough rheology; Mixograph; QTL